Common areas in development of multi-family housing - Brankov, Borjan D (Arhitektura i urbanizam, 2019)
The period of the 20th century is characterized by a large number of social changes, the development of industry, as well as changes in the structure of the traditional family. In addition, one of the major drivers of the need for new housing is the wartime destruction in Europe during two world wars. Significant housing shortage resulted in Mass housing development. This paper recognizes three different periods of development of multi-family housing, as a result of different changes during the 20th century. The first period represents the period after the First world war from the 1920s to the 1930s, the second period features industry involvement in housing around and after the Second world war from the 1930s to the 1950s and the third period centers around changes in spatial and cultural sphere of housing from the 1950s to the 1980s. Each time period is characterized by the progress or evolution of both problems that motivate the development of multi-family housing and innovative solutions for multi-family housing. Paper analyses three examples of built buildings from each time period. Each example is in a certain way an experimental architecture from its time and is distinguished by specific qualities and aspirations especially in the design of common areas of these buildings. The paper through selected examples of multi-family housing researches spatial manifestation of social and other changes. The focus of the analysis of the chosen buildings is on common areas, while the space of the dwelling is not subject to detail analysis. Each of the three periods is characterized by high innovation and an indication that multi-family housing can respond to requests and manifest new different ideas.